(untitled) (Medicine Today, 2022)
Introduction: Gallbladder disease is one of the most common surgical problems worldwide. About 10-15% of the adult western population has gallstone diseases . More than half a million cholecystectomies are performed per year in United States alone. Laparoscopic cholecystectomy (LC) is currently the most widely used surgical procedure for the treatment of gallstones. Aims and Objectives: To observe the cause of difficulties, the sequele , identify and find out the nature & rate of per operative complications and find out the type & frequency of early post-operative complications following laparoscopic cholecystectomy in acute calculous cholecystitis. Materials and Methods: This is a prospective interventional study which was conducted at Jashore Medical College Hospital & some clinics of the city from Sept 2019 to Feb 2020. A total of 100 patients underwent Laparoscopic cholecystectomy for acute calculous cholecystitis within 7 days of admission. Results:Among 100 patients, 80 females & 20 males with maximum age group were in the fourth decade, Laparoscopic cholecystectomy was done in 97 (97%) cases & in 3(3%) cases conversion were needed, none of the patients were developed major Per & postoperative complications. Peroperative complication rate was 22 (22%) with conversion was 03(3%) cases. All of the above complications were managed accordingly & successfully. Conclusion: Laparoscopic Cholecystectomy is a safe, effective procedure for the early management of patients with acute calculus cholecystitis. Meticulous dissection & good exposure of callot’s triangle, posterior clearance may prevent bile duct injuries. Medicine Today 2022 Vol.34(1): 39-43